THE USED OF ISDA (INTAN’S SCREENING DIAGNOSTIC ASSESMENT) IN NURSING CARE FOR THALASEMIA - Edi Wibowo (UNEJ e-Proceeding, 2017)
Background: Thalasemia is a chronic disease and mostly found in children. Thalassemia patients need some treatment in term of blood transfussion and desferal in their whole life. Hence, the nurse has an important role in conducting nursing care for the patient at the hospital. During May 2016, report showed that there were 29 thalassemia patients in Jombang Distric Hospital (RSUD), to do blood transfussion. Methods: The research method was analytic survey research with cross sectional survey design by explorative approach. The location of the research was Jombang Distric Hospital (RSUD). This was conducted in 2017 and the population was the children with thalassemia. The sample was taken by proposive sampling technique and the total was 10 respondents. Results: The research showed that the children with thalassemia had 100% tissues perfussion disorder, 50% malnutrition and 90% growth and development. Hence the combining used of ISDA, NANDA and SDKI can help the researcher in assessing the data validity. Therefore, it is important for the nursing student to use ISDA,NANDA,NIC,NOC and SDKI in doing their nursing care paper. Keywords: Thalassemia, ISDA